LEAFDATA: a literature-curated database for Arabidopsis leaf development - Szakonyi, Dóra (2016)
In the post-genomic era, biological databases provide an easy access to a wide variety of scientific data. The vast quantity of literature calls for curated databases where existing knowledge is carefully organized in order to aid novel discoveries. Leaves, the main photosynthetic organs are not only vital for plant growth but also essential for maintaining the global ecosystem by producing oxygen and food. Therefore, studying and understanding leaf formation and growth are key objectives in biology. Arabidopsis thaliana to this date remains the prime experimental model organism in plant science.